Postcolonial contraventions - Chrisman, Laura (Manchester University Press, 2023)
Both polemical and scholarly, this text is challenging in its analysis of black Atlantic studies, colonial discourse analysis and postcolonial theory. Chrisman provides important paradigms for understanding imperial literature, Englishness, and black transnationalism.Both polemical and scholarly, this text is challenging in its analysis of black Atlantic studies, colonial discourse analysis and postcolonial theory. Chrisman provides important paradigms for understanding imperial literature, Englishness, and black transnationalism.